The Implementation of Simulation Method in Training Program for Improving Biologi Teacher Skills in Using Local Environment as Learning Resources - Agus Asep Sulaeman (Universitas Negeri Yogyakarta, 2018)
Biology teacher needs to integrate the outdoor contexts into an authentic curriculum to improve students' positive orientation toward science. Therefore, the purpose of this study is to describe the implementation of the simulation method in teacher training program to improve Biology teacher's skills in using the outdoor environment as learning resources. The study employed a single class experimental method conducted in April 2016. The subjects were 36 Biology teachers from Yogyakarta, Central Java, and East Java Provinces. The data collected were the ability of teachers in using the environment as learning resources obtained by assessing the learning guide documents using the product assessment instrument; the concept acquisition was gained using thirty multiple choice items containing four choiceas of answers. The data were analyzed by t-test resulted in significance level of 0,05. In addition, participants' responses were also collected using training evaluation questionnaires, which were then analyzed using descriptive quantitative. The study showed that the ability of teachers in using the outdoor environment as learning resources was good. On the other hand, the concept acquisition of teachers was significantly increasing (mean score of pretest 58.17 and postes 79.18) and teachers responded very well to all aspects of training implementation.